Nonlinear Interaction of Magnetoacoustic Modes in a Quasi-Isentropic Plasma Flow - PERELOMOVA, Anna (Archives of Acoustics, 2021)
The nonlinear interaction of magnetoacoustic waves in a plasma is analytically studied. A plasma is an open system. It is affected by the straight constant equilibrium magnetic flux density forming constant angle with the wave vector which varies from 0 till π. The nonlinear instantaneous equation which describes excitation of secondary wave modes in the field of intense magnetoacoustic perturbations is derived by use of projecting. There is a diversity of nonlinear interactions of waves in view of variety of wave modes, which may be slow or fast and may propagate in different directions. The excitation is analysed in the physically meaningful cases, that is: harmonic and impulsive exciter, oppositely or accordingly directed dominant and secondary wave modes.